Automated technique for the estimation of fetal haemoglobin. Issue 6 (June 1974) - Brook, S. R.; Crane, R. S.; Huntsman, R. G.; Marshall, T. D. De C.; McLellan, D. S.; Semple, M. J.
Abstract : An automated alkali denaturation technique which measures fetal haemoglobin is described. This method offers greater speed and a lower standard deviation than comparable manual methods.